Knowledge on therapies for pressure ulcer: an integrative review - Rosana Freitas Azevedo; Rosana Maria Pereira Garcia; Maria Thaís Calasans (Universidade Federal do Ceará, 2021)
Objective: to analyze the evidences on therapies for the treatment of pressure ulcers. Methods: integrative review with articles published between 2014 and 2019 in SciELO, MEDLINE, LILACS, BDENF, IBECS and CINAHL databases. The descriptors used were: pressure ulcer, therapeutics and nursing care. Results: twelve articles were found that met the study´s objectives. Data from the eligible studies were extracted using the data collection instrument. After this step, they were categorized and synthesized, in a descriptive way, and listed in four categories: professionals' knowledge about therapies; adequate management of therapies; therapies with biophysical agents; and non-conventional therapies. Conclusion: the analyzed articles reflect on the use of some therapies and strategies to treat pressure ulcers. The various therapies addressed in the research on the treatment of these ulcers proved to be effective, however, they are insufficient to ensure their wide and safe use.